Caracterização da arquitetura interna das bacias do Vale do Cariri (NE do Brasil) com base em modelagem gravimétrica 3-D - Castro, D. L. de (2022)
An inversion method for three-dimensional modeling of gravity anomalies has been applied in the main intracratonic basins of Northeastern Brazil. These NE trending sedimentary basins of Cretaceous age are located in the Cariri Valley, in Ceará, Paraíba, and Pernambuco states, NE Brazil. The gravity stations database was obtained by several geophysical surveys carried out by Brazilian universities and geological government agencies. A complementary gravity survey was conducted by the “Laboratório de Geofísica de Prospecção e Sensoriamento Remoto” (LGPSR) of Ceará State University and “Instituto Brasileiro de Geografia e Estatística” (IBGE) to improve the distribution of gravity stations in the study area. The iterative interpretation technique was applied to the gravity anomalies of the Cariri Valley, which resulted in reliable estimates of the internal geometry of the rift basins. The gravity models indicate a strong structural control of pre-existing upper crustal weakness zones in the development of the graben architecture of the basins. This provides additional arguments to the hypothesis of extensive Neoproterozoic shear zone reactivation during the Mesozoic rifting process, whose evolution resulted in the South America - Africa separation and the opening of the Atlantic Ocean.